Application domain ontology-based transformation to database design - Trinkūnas, Justas; Vasilecas, Olegas (Lietuvos matematikos rinkinys, 2021)
The paper analyses graph oriented ontology transformation into conceptual data model. A number of methodswere proposed to develop conceptual datamodels, but only fewdealswith knowledge reuse. In this paperwe present an approach for knowledge represented by ontology automatic transformation into conceptual data model. The graph transformation language is presented and adapted for formal transformation of ontology into conceptualmodel. Details and examples of proposed ontology transformation into conceptual data model are presented.
Keywords: ontology; conceptual modelling; transformation